KOMUNIKASI INFORMAL, GAJI, DAN MOTIVASI KERJA KARYAWAN DI PT INDONUSA ALGAEMAS PRIMA BALI - Cynthia Febriana; Eddy M. Sutanto (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2015)
The aim of this research was to test whether informal communication and salary affected employee's work motivation in PT Indonusa Algaemas Prima Bali. The population and samples of this research were 84 employees as this research used saturated method sampling with a quantitative approach using a multiple linear regression analysis. The results indicated that informal communication and salary had a positive and significant impact to employee's work motivation in PT Indonusa Algaemas Prima Bali both partially and simultaneously.